2020
DOI: 10.21203/rs.3.rs-59585/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protective Effects of Ginkgo Biloba Dropping Pills Against Liver Ischemia/reperfusion Injury in Mice

Abstract: Background: Liver ischemia-reperfusion (I/R) injury is an inevitable pathological phenomenon in various clinical conditions, such as liver transplantation, resection surgery, or shock, which is the major cause of morbidity and mortality after operation. Ginkgo Biloba Dropping Pill (GBDP) is a unique Chinese Ginkgo Biloba leaf extract preparation that exhibits a variety of beneficial biological activities. The aim of this study is to investigate the protective effects of GBDP on the liver I/R injury both in vit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…In Wang's study, it was shown that the Ginkgo biloba Dropping Pill (GBDP) can inhibit the expression of apoptosis-related protein markers in vitro. Consistent with the results of in vitro experiments, animal experiments confirmed that GBDP can downregulate the expression of proapoptotic proteins and reduce hepatocyte apoptosis caused by liver I/R injury [22].…”
Section: Antiapoptosissupporting
confidence: 84%
“…In Wang's study, it was shown that the Ginkgo biloba Dropping Pill (GBDP) can inhibit the expression of apoptosis-related protein markers in vitro. Consistent with the results of in vitro experiments, animal experiments confirmed that GBDP can downregulate the expression of proapoptotic proteins and reduce hepatocyte apoptosis caused by liver I/R injury [22].…”
Section: Antiapoptosissupporting
confidence: 84%
“…In this study, we report the in vitro inhibition test of the RevX solution extract on SARS-CoV-2 M pro and the results of molecular docking of putative candidates. The results show that the solid fraction can strongly inhibit the hydrolytic activity of M pro , which indicates that the solid fraction might prevent the replication of SARS-CoV-2 by inhibiting the enzymatic activity of M pro ( Shaito et al, 2020 ; Wang et al, 2020 ). The molecular docking of MS identified components shows that the three sterol-like compounds are suitable for the putative active site pocket.…”
Section: Resultsmentioning
confidence: 92%
“…Model Construction of Liver IR Injury. An established mouse model of 70% warm hepatic IR injury was used (16). Briefly, the hepatic artery and portal vein were isolated and clipped with a microvascular clamp, occluding blood supply to the left and middle liver lobes.…”
Section: Animal Models Of Liver Diseasementioning
confidence: 99%